Knowledge as a factor of consolidation and development of society - Levko, Anatolii I. (Journal of the Belarusian State University. Sociology, 2019)
The article presents the analysis of the existing theoretical-methodological paradigms, scientific disciplines and concepts of historical and modern research of knowledge as an important social-cultural factor of consolidation and development of society. It shows the dependence of the existing forms of gaining knowledge, including education, on the correlation of knowledge with information, human needs and culture of society. There is substantiated the need of the sociological diagnosis of time as an effective way to solve the existing problems and the main condition of building adequate scientific systems and models of education.
Keywords: knowledge; information; culture; consciousness; rationality; anthropology of knowledge; sociology of knowledge; praxeology of knowledge; typology of sciences; I-concept